Performance of Able-Bodied Subjects on a Text-Typing Task Using a Head-Operated Device and Expanded Membrane Cursor Keys - Capilouto, Gilson J.; McClenaghan, Bruce; Williams, Harriet G.; Dickerson, John; Hussey, James R. (Perceptual and motor skills, 2004)
Children and adults with disabilities frequently rely on computers to complete written tasks. Those with significant motor limitations typically use alternative computer-input devices since the traditional keyboard and mouse are insufficient to accommodate their abilities. For persons unable to isolate their fingers, input devices controlled by movements of the head or whole hand or arm movements may be among the options considered. This study investigated the performance of a head-operated device and expanded membrane cursor keys for text entry. Data from 24 young adults indicated the head-operated device performed significantly faster given reduced cognitive demands for device operation, increased stimulus–response compatibility, and simplicity of movement. Use of the expanded membrane cursor keys resulted in significantly lower error rates. No significant differences in comfort or ease of use were reported for the two devices. The relative performance of device options for users sharing similar motor challenges provides rehabilitation specialists with important clinical information.